Diurnal variation of frequency domain T‐wave alternans on 24‐hour ambulatory electrocardiogram in subjects without heart disease: Significant effect of autonomic nervous activity of the heart. Issue 3 (7th November 2018) - Hashimoto, Kenichi; Kasamaki, Yuji; Soma, Masayoshi; Takase, Bonpei
Abstract: Background: T‐wave alternans (TWA) is a risk stratification predictor for sudden cardiac death. However, little is known about the diurnal variation of TWA. Whether TWA are affected by heart rate (HR) or cardiac autonomic nervous activity in the subjects without significant structural heart disease in daily life is not fully understood. Thus, this study was aimed to clarify these issues. Methods: Frequency domain (FD)‐TWA analysis was conducted in 47 subjects without significant structural heart disease using 24‐hr ambulatory electrocardiogram (AECG). Measurement of heart rate variability (HRV) was performed in order to evaluate the autonomic activity of the heart. The maximum FD‐TWA value in each period was measured four times per day (A, 00:00–6:00 hr; B, 06:00–12:00 hr; C, 12:00–18:00 hr; D, 18:00–24:00 hr). Correlations between FD‐TWA and either HR or HRV parameters (LF/HF, LFnu, HFnu, SDNN, CVNN, pNN50) were analyzed in each period (A‐D). Results: There was diurnal variation of FD‐TWA (median, inter‐quartile range [IQR]: A, 8.2 [6.5, 10.6] μV; B, 10.1 [8.4, 15.0] μV; C, 17.6 [12.3, 25.0] μV: D, 11.9 [9.1, 19.9] μV; p  < 0.0001). Maximum FD‐TWA had positive correlations with HR and LF/HF (HR, r  = 0.496, p  < 0.0001; LF/HF, r  = 0.414, p  = 0.004), while FD‐TWA had a negative correlation with HFnu ( r  = −0.291, p  = 0.048). On multiple linear regression analysis, HR had an independent effect on log FD‐TWA amplitude (β = 0.461, p  = 0.001). Conclusions: FD‐TWA has marked diurnal variation in the daily life of the subjects without significant structural heart disease. This variation could be more strongly affected by HR than the HRV indices.